2019
DOI: 10.3390/s19245404
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Data Logger for Capturing Human-Machine Interaction in Wheelchair Head-Foot Steering Sensor System in Dyskinetic Cerebral Palsy

Abstract: The use of data logging systems for capturing wheelchair and user behavior has increased rapidly over the past few years. Wheelchairs ensure more independent mobility and better quality of life for people with motor disabilities. Especially, for people with complex movement disorders, such as dyskinetic cerebral palsy (DCP) who lack the ability to walk or to handle objects, wheelchairs offer a means of integration into daily life. The mobility of DCP patients is based on a head-foot wheelchair steering system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In addition, researchers have used technologies originally developed for mobile robots to create smart wheelchairs that reduce the physical, perceptual, and cognitive skills necessary to operate a power wheelchair for individuals with severe dysfunction disorders such as amyotrophic lateral sclerosis (ALS), spinal cord injury (SCI), and muscle dystrophy (MS) [ 13 , 49 ]. Different kinds of input methods, such as joysticks [ 2 , 50 ], voice commands [ 51 , 52 ], the sip-and-puff interface [ 6 ], BCI [ 9 , 10 , 17 , 43 ], the tongue drive system (TDS) [ 7 , 8 , 32 , 33 , 34 , 35 ], the head gesture based interface (HGI) [ 53 , 54 ], the eye-controlled interface [ 3 , 39 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], the EMG-based interface [ 62 , 63 ], and the multimodal interface [ 64 , 65 ], have been used in EPW HMI to accommodate the disabled. Some examples of the remarkable technological advances in EPW HMI methodology in recent years are shown in detail in Figure 8 .…”
Section: Bibliometric Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, researchers have used technologies originally developed for mobile robots to create smart wheelchairs that reduce the physical, perceptual, and cognitive skills necessary to operate a power wheelchair for individuals with severe dysfunction disorders such as amyotrophic lateral sclerosis (ALS), spinal cord injury (SCI), and muscle dystrophy (MS) [ 13 , 49 ]. Different kinds of input methods, such as joysticks [ 2 , 50 ], voice commands [ 51 , 52 ], the sip-and-puff interface [ 6 ], BCI [ 9 , 10 , 17 , 43 ], the tongue drive system (TDS) [ 7 , 8 , 32 , 33 , 34 , 35 ], the head gesture based interface (HGI) [ 53 , 54 ], the eye-controlled interface [ 3 , 39 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ], the EMG-based interface [ 62 , 63 ], and the multimodal interface [ 64 , 65 ], have been used in EPW HMI to accommodate the disabled. Some examples of the remarkable technological advances in EPW HMI methodology in recent years are shown in detail in Figure 8 .…”
Section: Bibliometric Results and Discussionmentioning
confidence: 99%
“… Examples of the remarkable technological advances in EPW HMI methodology in recent years. ( a ) A wheelchair data logger: proposed to capture data from human-wheelchair interaction for the head-foot steering system [ 54 ] (Reprinted with permission from ref. [ 54 ].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…12,16 As such, the use of PWs could enhance their activity and participation at school, outdoors, and in the community, however, several burdens and challenges are present. 16,19,20 In this respect, clinical practice supports the use of an alternating steering method like the use of head/foot steering wheelchairs, whereas basal movements of the head and the feet seem to be better controlled in DCP than the more difficult control movement of the arms. 1 That is, children with DCP could use their head to steer the wheelchair to the right and to the left, and their feet to accelerate and brake.…”
Section: Introductionmentioning
confidence: 99%
“…1 That is, children with DCP could use their head to steer the wheelchair to the right and to the left, and their feet to accelerate and brake. 20 To date, however, PW mobility training with head/foot steering wheelchairs in DCP is solely based on clinical expertise where lack of evidence-based knowledge results in unstandardized mobility training and long learning curves. 13,21,22 A previous study in CP participants with severe bilateral involvement showed that the level of power mobility independence is related to the length of training time and not to the participants' intellectual and functional abilities.…”
Section: Introductionmentioning
confidence: 99%